ADSORPTION OF Th-232 AND U-238 BY γ- Al2O3-HUMATE AT SINGLE AND COMPETITIVE SYSTEMS - Muzakky Muzakky; Sri Juari Santosa (Indonesian Journal of Chemistry, 2008)
The calculation experiments of adsorption capacities of Th-232 and U-238 in γ- Al2O3-humate at single system and competitive with Freundlich method has been done. The purpose of the research is (1) to characterize γ- Al2O3-humat functional groups, (2) to know γ- Al2O3-humat solubility and (3) to predict adsorption capacities of U-238 and of Th-232 at adsorbent γ-Al2O3-humate. The characterization of functional groups γ- Al2O3-humate is done by Fourier Transform Infra red (FTIR) Spectrometry. Based on perception results of functional spectra characteristic of γ-Al2O3-humate is similar with humic substance with decrease at stretching -OH at 3400 - 3300 cm-1, and C=O stretching of COOH spectra, C=C aromatic or hydrogen bond of C=O at 1725-1720 cm-1spectra. The solubility testing of γ-Al2O3-humate indicated that the compound it's effective used as adsorption U-238 and of Th-232 at pH 1 to 4 conditions. At single adsorption system with 1000 mg/L of U-238 or Th-232 feed, 0.001 g up to 0.1 g weight of γ-Al2O3-humate were got for U-238 balanced to 992.15 mg/L and 980.66 mg/L for Th-232.  By using regression line curve between ln C and ln x/m, adsorption capacities of U-238 and Th-232 at single system can be calculated as 3.63 mg/g and 2.93 mg/g, respectively, while adsorption capacity of Th-232 was increases to 8.08 mg/g and U-238 decreases to 0.91 mg/g at competitive system.